2013
DOI: 10.24059/olj.v17i4.385
|View full text |Cite
|
Sign up to set email alerts
|

Building a Foundation for Success Through Student Services for Online Learners

Abstract: Retaining students in distance education programs requires institutions to field a strategically aligned, cross-unit team able to provide streamlined and effective services to online learners throughout the student's academic life (from applicant to alumni). If any team member drops the ball during interaction with the online student, the student becomes frustrated or distracted, and student retention is jeopardized. In today's highly competitive marketplace, students have a "universe of opportunities" for obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 7 publications
(11 reference statements)
1
10
0
Order By: Relevance
“…Existing research has demonstrated that isolation can be problematic for online students. Online students often feel isolated since they are not meeting in person at brick-and-mortar environments (Ali & Kohun, 2007;Hoffman, 2014;Newberry & DeLuca, 2013). Prior research also indicated that interconnectedness and interactions with others are critical components of dissertation completion (Baker et al, 2013;Lovitts, 2001;Rovai, 2002;Sull, 2013;Vekkaila et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing research has demonstrated that isolation can be problematic for online students. Online students often feel isolated since they are not meeting in person at brick-and-mortar environments (Ali & Kohun, 2007;Hoffman, 2014;Newberry & DeLuca, 2013). Prior research also indicated that interconnectedness and interactions with others are critical components of dissertation completion (Baker et al, 2013;Lovitts, 2001;Rovai, 2002;Sull, 2013;Vekkaila et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that when doctoral students have access to faculty and the faculty spend time with the students, it contributes to student' success (Bagaka's, Badillo, Bransteter, & Rispinto 2015;Hoffman, 2014). It is advantageous for students to develop relationships with faculty because, through that association, it is likely they will receive more support and resources, enabling degree completion (Newberry & DeLuca, 2013). Mitigat-ing potential distance barriers and cultivating a means of collaboration between online doctoral students and faculty can be essential for doctoral students' success.…”
Section: Online Doctoral Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey was created after reviewing the literature and other existing instruments (i.e., Dare, Zapata, & Thomas, 2005;Lee, Choi, & Kim, 2013;Newberry & DeLuca, 2014;Rovai, 2003). We used portions of Rovai's Composite Persistence Model as the conceptual framework for the design of the survey and most of Dare, Zapata, and Thomas's (2005) survey questions and format for the development of our survey questions.…”
Section: Instrumentmentioning
confidence: 99%
“…2003; Newberry & DeLuca, 2014). The micro perspective also includes issues surrounding instructor preparedness, such as online pedagogy (Goodyear, Salmon, Spector, Steeples, & Tickner, 2001;Rovai, 2004;Schrum, 2000), facilitation and online presence (Keengwe & Kidd, 2010;Travis & Rutherford, 2012Young, 2006), and addressing faculty resistance to teaching online (Mitchell, Parlamis, & Clairborne, In press).…”
Section: Individual Contributors To Online Learning Successmentioning
confidence: 97%